Analysis of The Impact of IFRS Adoption on Value Relevance: A Structured Literature Review Approach - Dedyansyah, Achmad Farid; Kartikasari, Evi Dwi; Indira, Irma (Islamic Accounting Journal, 2026)
Objective & object: This study aims to analyze and synthesize previous research findings regarding the adoption of the International Financial Reporting Standards (IFRS) on value relevance in improving the quality of accounting information of companies across countries. The object of this study consists of international scholarly articles discussing the relationship between IFRS adoption and value relevance, published between 2011 and 2022. Methods: In this research, a SLR methodology is taken into consideration by applying a systematic process for the identification, selection, and analysis of rest relevant studies. The selection criteria are related to the journal field, the year of the publication, the country sample, and the methodological approach. The empirical analysis is segregation by region Europe, Asia, Africa, America, and Oceania and regression based methodologies dominate Results & Conclusions: The results suggest that the positive effect of IFRS adoption on value relevance is pronounced in those countries in Europe and America which have adopted full IFRS. To the contrary, in most developing countries in Asia and Africa, the effects are weak due to the poor reporting infrastructure and the underdeveloped system of financial governance. Limitations: The limitation of this study is that the years of literature are limited and only English article are included, sensing that may be missing other relevant original studies in other languages. Implications: The findings of this study are directly useful to the regulators and accounting standard setters as a scientific support to validate and reinforce the adoption of IFRS as an international financial reporting standard.